2010
DOI: 10.1111/j.1365-3180.2010.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference between maize and Xanthium strumarium or Datura stramonium

Abstract: Xanthium strumarium and Datura stramonium are two of the most important weeds of maize in Iran. Their growth was compared in a field study conducted over 2 years. Relationships were derived between weed density and crop yield, yield components and various growth parameters. Yield, grain number ear )1 and grain weight were affected more by X. strumarium than by D. stramonium. Xanthium strumarium followed a pattern of growth resembling that of the maize, whereas D. stramonium continued growing for a longer perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Also, because of its large size, high spatial uniformity is common in maize production, but not in other cereals. Early in the growing season, maize is usually a good competitor against weeds (Page et al ., ), even against some perennial weeds, such as Datura stramonium L. (jimson weed) and Cannabis sativa L. (marijuana; Cavero et al .,; Karimmojeni et al ., ; Lehoczky et al ., ), as well as annuals such as Chenopodium album L. (lambs quarters), Xanthium strumarium L. (cocklebur) and Abutilon theophrasti Medik. (velvetleaf; Baghestani et al ., ; Karimmojeni et al ., ; Lindquist & Mortensen, ; McDonald & Riha, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, because of its large size, high spatial uniformity is common in maize production, but not in other cereals. Early in the growing season, maize is usually a good competitor against weeds (Page et al ., ), even against some perennial weeds, such as Datura stramonium L. (jimson weed) and Cannabis sativa L. (marijuana; Cavero et al .,; Karimmojeni et al ., ; Lehoczky et al ., ), as well as annuals such as Chenopodium album L. (lambs quarters), Xanthium strumarium L. (cocklebur) and Abutilon theophrasti Medik. (velvetleaf; Baghestani et al ., ; Karimmojeni et al ., ; Lindquist & Mortensen, ; McDonald & Riha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Early in the growing season, maize is usually a good competitor against weeds (Page et al ., ), even against some perennial weeds, such as Datura stramonium L. (jimson weed) and Cannabis sativa L. (marijuana; Cavero et al .,; Karimmojeni et al ., ; Lehoczky et al ., ), as well as annuals such as Chenopodium album L. (lambs quarters), Xanthium strumarium L. (cocklebur) and Abutilon theophrasti Medik. (velvetleaf; Baghestani et al ., ; Karimmojeni et al ., ; Lindquist & Mortensen, ; McDonald & Riha, ). It has been hypothesised that this is because maize has a high leaf area index, allowing it to shade weeds effectively (Cavero et al ., ; McDonald & Riha, ; McDonald et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Other than environmental variables, the most important constraint to maize yield and thus economic returns is competition from weeds (Rajcan & Swanton 2001;Karimmojeni et al 2010). Weed competition results from the use of widely spaced maize rows, which allow a high portion of ambient light to penetrate.…”
Section: Research Articlementioning
confidence: 99%
“…This species is generally highly-competitive for nutrients, light and moisture and can drastically reduce yield, harvesting efficiency, and crop quality due to seed contamination (Gossett, 1971). In soybean fields, this species can reduce yields up to 80% (Bloomberg et al, 1982), while yield reduction in corn ranged from 30 to 40% (Karimmojeni et al, 2010). Nakova et al (2004) confirmed the significance of this invasive species as a weed in corn across the Balkan Peninsula.…”
Section: Introductionmentioning
confidence: 66%